PANCASILA ECONOMIC SYSTEM A LEGAL REFORM IN GLOBALIZATION ERA - Bina Era Dany; Teuku Daudsyah (Jurnal Pembaharuan Hukum, 2022)
Pancasila is the source of all legal sources that form the basis for the implementation of the economic system in Indonesia. The purpose of this study is to find out and analyze the economic legal system based on Pancasila which is the basis of the nation's ideology and the basic norms of the Indonesian nation in the era of globalization. the research method uses a normative juridical approach. The results of the study state that the renewal of economic law in Indonesia must be directed to create people's welfare, by relying on the values of Pancasila as the philosophy and way of life of the nation which becomes the guideline in the implementation of every aspect of the life of the nation, state and society. Pancasila contains the principle of gotong royong, and that is actually the core of the renewal of economic law which places mutual cooperation as a value that must be realized in the formulation of laws and regulations which then become the basis for realizing social welfare.